Atividade da enzima alfa-amilase salivar e variáveis psicológicas em pacientes com ulceração aftosa recorrente - Cardoso, Juliana Andrade (2013)
This study aimed at analyzing the activity of the salivary alpha-amylase enzyme (SAA), levels of stress and anxiety of patients with recurrent aphthous stomatitis (RAS), as well as the impact of this disease on the life quality. The sample consisted of 52 adult patients, distributed in RAS group (n=22) and control group (n=30), matched for sex and age. For the investigation of stress symptoms the Lipp s Inventory of Stress Symptoms for Adults and for anxiety, the Beck Anxiety Inventory were used. The World Health Organization Quality of Life-bref (WHOQOL-BREF) and the Oral Health Impact Profile-14 (OHIP-14) tests were used to evaluate the overall life quality and the life quality related to oral health respectively. Saliva samples were collected in the morning and afternoon and the activity of the salivary alpha-amylase enzyme was analyzed by enzymatic kinetic method with the Salivary α-Amylase Assay Kit. No significant difference was observed between groups regarding the SAA activity (P=0.306) in the morning or afternoon samples. Patients in the RAS group had higher scores of anxiety (P=0.016) and, although the prevalence of stress has been higher in this group, there was no significant difference compared to the control group (P=0.498). The scores of physical (P=0.026), psychological (P=0.005), social (P=0.001) and environmental (P=0.040) domains of the WHOQOL-BREF inventory were significantly lower in patients with RAS. The values obtained through OHIP-14 were significantly higher in these patients (P=0.002). We can conclude that RAS negatively affects the life quality of individuals. Patients with the disease have higher levels of anxiety, suggesting its possible association with the etiopathogenesis of RAS. Moreover, despite being a biomarker of stress, the release of SAA oscillates 11 rapidly and may be influenced by several factors, not being efficient for the evaluation of psychological changes in patients with RAU in this study.